Comparison of Ethereum Smart Contract Vulnerability Detection Tools - Aryal, Binod (My University, 2021)
The thesis aims to reflect on the technical aspects of the Blockchain and Ethereum Smart Contract Vulnerabilities. The thesis has provided an in-depth overview of blockchain technologies, focused on Bitcoin, Ethereum needed to understand for vulnerabilities in blockchain. Application of cryptographic functions, consensus algorithm is explained and Blockchain security vulnerabilities are presented. A summary of public and private blockchains are shown, how these differ from each other and what are the use cases for these various blockchain application is provided. Ethereum Smart Contract are introduced and explained. The vulnerabilities present in smart contract are researched empirically. The second half of thesis is focused on finding security flaws and vulnerabilities on Ethereum Smart contract. The attack vectors that are possible, cyber-attacks which has already happened and how can they be mitigated, if found, are presented. Analysis and comparison of popular Ethereum Smart Contract Vulnerability detection tools has been empirically studied using an automated tool called SmartBugs and the results are presented.
Keywords: Blockchain Security, Ethereum Smart Contract Vulnerabilities, Smart Contract Security tools